Lessons on synthetic bioarchitectures : interaction of living matter with synthetic structural analogues /: interaction of living matter with synthetic structural analogues. ([2018]) - Ehmoser-Sinner, Eva-Kathrin; Tan, Cherng-Wen Darren
No abstract available